Non‐Thermal Plasma Activation of Gold‐Based Catalysts for Low‐Temperature Water–Gas Shift Catalysis. (12th April 2017) - Stere, Cristina E.; Anderson, James A.; Chansai, Sarayute; Delgado, Juan Jose; Goguet, Alexandre; Graham, Willam G.; Hardacre, C.; Taylor, S. F. Rebecca; Tu, Xin; Wang, Ziyun; Yang, Hui
Abstract: Non‐thermal plasma activation has been used to enable low‐temperature water‐gas shift over a Au/CeZrO4 catalyst. The activity obtained was comparable with that attained by heating the catalyst to 180 °C providing an opportunity for the hydrogen production to be obtained under conditions where the thermodynamic limitations are minimal. Using in situ diffuse reflectance infrared Fourier transform spectroscopy (DRIFTS), structural changes associated with the gold nanoparticles in the catalyst have been observed which are not found under thermal activation indicating a weakening of the Au−CO bond and a change in the mechanism of deactivation.